2022
DOI: 10.1002/app.52478
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously improving toughness and hydrophobic properties of cycloaliphatic epoxy resin through silicone prepolymer

Abstract: To improve the toughness and hydrophobic property of the cycloaliphatic epoxy resin (CEP), which is vital to application in high voltage insulation of outdoor transmission lines, 3-aminopropyltriethoxysilane was used as the intermediate to prepare the silicone prepolymer by the interaction of the end groups of the CEP and the hydroxy-terminated polydimethylsiloxane. The results showed that the silicone prepolymer segments were self-assembled to form solid dispersion phases distributed uniformly in the CEP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…When 5% SITEUP is incorporated, the contact angle of the thermosets reaches 94°, which indicates the thermoset has changed from a hydrophilic material to a hydrophobic surface; 20% of SITEUP reaches 110°. Liu et al [ 53 ] revealed that surface tension has a close relationship with the static contact angle of a clean solid surface. The siloxane segments in the main chain of the silicones are surrounded by non-polar aliphatic groups (Si-CH 3 ), contributing to the low surface tension of this material [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…When 5% SITEUP is incorporated, the contact angle of the thermosets reaches 94°, which indicates the thermoset has changed from a hydrophilic material to a hydrophobic surface; 20% of SITEUP reaches 110°. Liu et al [ 53 ] revealed that surface tension has a close relationship with the static contact angle of a clean solid surface. The siloxane segments in the main chain of the silicones are surrounded by non-polar aliphatic groups (Si-CH 3 ), contributing to the low surface tension of this material [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The alicyclic epoxy resin samples used in this paper are made by an automatic pressure gel molding process by a manufacturer [20][21][22]. The formula and process of the test sample are the same as that of the 110 kV alicyclic epoxy insulator sheath produced by the manufacturer, and the HTVSR sample is produced by Dalian Insulator Group Co., Ltd. (Dalian, China).…”
Section: Experimental Work 21 Materialsmentioning
confidence: 99%
“…Epoxy resin insulation materials, a kind of polar polymer material, have been extensively applied in many electrical equipment such as power electronic packaging, outdoor insulation, and power cable , due to the excellent insulation strength, mechanical properties, and processability. The epoxy resin encapsulated products are inevitably invaded by moisture or water during long-term service, leading to the deterioration of the epoxy resin insulation materials.…”
Section: Introductionmentioning
confidence: 99%